PENGUATAN PERAN PEMERINTAH DAN MASYARAKAT DALAM PENCEGAHAN KEKERASAN TERHADAP ANAK - Fadlan Harmein Harahap; Faisar Ananda (IJTIMAIYAH Jurnal Ilmu Sosial dan Budaya, 2026)
This study aims to comprehensively analyze the synergy between the roles and functions of government and society in the child protection system in Indonesia. Using an empirical legal approach and qualitative research methods, this study examines the implementation of child protection policies at the structural and cultural levels, while identifying factors that distort their effectiveness in the field. Data collection was conducted through in-depth interviews with policymakers, legal practitioners, and community leaders, combined with document studies of regulations and data on child abuse cases. The results indicate that although the government has adequate regulatory instruments, policy execution at the grassroots level is often disoriented due to weak inter-agency coordination and limited resources. Furthermore, the community's oversight function as the first line of defense has not been optimal due to a persistent culture of social apathy and the perception that domestic violence against children is a private matter. This study concludes that ideal child protection requires the reconstruction of an integrative partnership between the government as a regulatory facilitator and the community as an active observer. This research recommendation points to the importance of strengthening local institutional capacity and massive public education to erode social permissiveness towards children's rights violations.